Composite Organic materials used as reinforcement for fluid handling pipelines - LATORRE, G.; VARGAS, F. (CT&F - Ciencia, Tecnología y Futuro, 1999)
This paper presents the experimental test and the results of the development of a composite organic material (MCO) for the reinforcement and covering of pipelines. MCO is desinged to be applied to pipelines with external, damages such as dents or gauges or with surface damages caused by corrosion. The product can recover transport lines with 65% thickness losses due to corrosion in lenghts of less than 0,2 m. The system developed by Ecopetrol-ICP can stop progressive picking corrosion, it has an excellent capillary, good adhesion, good resistance in cathodic protection, and mechanical strength that can support the operational pressure of the pipeline. MCO is a mixture of a polymeric resin reinforced with organic fibers, it can be applied to surface or underground pipelines without stopping normal operation. The maximum rupture pressure attained by the MCO was 23,4 MPa in pipelines with a 65% tickness loss due to corrosion. The normal operation pressure is 1 0 - 1 2 MPa.